Against Memetics - Boroch, Robert (Hybris, 2011)
Przeciw Memetyce (Against Memetics) Article is a critical analysis of theoretical foundations of memetics from the perspective of 2010. In my study, I mainly discuss assumptions adopted by Polish memeticians (papers published mostly in the magazine „Teksty z Ulicy. Zeszyty memetyczne”). The article concerns “biological foundations” of memetics adopted by the researchers, which causes a transfer of the biology’s conceptual paradigm exactly to the field of memetics, since a) the research methodology of memetics has been based on achievements of virology (sic!); whereas, b) memetics itself has been called a scientific theory and; therefore, c) the subject of memetics has been determined and that is the evolution of culture. What is more, the article discusses the issue of so-called qualia. Joining the theory of memes-replicators with qualia is risky; nevertheless, it is not completely unjustified; especially, as memeticians attribute features of qualia to memes. Finally, the deliberations on memes and memetics are directed towards semiotics assuming the understanding of a group of memes as a code of a specific semantic deposit SD, which forms ℝ relation in a specific knowledge representation RW.